Hypertonic Dextrose Prolotherapy Injection in Grade IV Knee Osteoarthritis with Obesity: A Case Report - Juwita Raudlatul Salsabil; Rita Vivera Pane; Hasan Hasan; Aufar Zimamuz Zaman Al Hajiri (Interna Publishing, 2024)
The main complaint in knee osteoarthritis (KOA) is knee pain and limited range of motion (ROM) which affects the patient's quality of life. Dextrose prolotherapy successfully reduced pain and enhanced functional status and quality of life in chronic knee pain, which is classified as KOA grade II or III by the Kellgren-Lawrence classification. We present a case of grade IV KOA with co-morbid obesity who refused surgical management but got dextrose prolotherapy instead. She received prolotherapy for the right knee 5 times with a gap of 4 weeks between treatments. Western Ontario and McMaster Universities Osteoarthritis (WOMAC score), Numerical Rating Scale (NRS), knee ROM, Barthel index, count test, and Timed Up and Go Test (TUG) were evaluated 1 day after each treatment and compared to each post-injection score. This patient is also comorbid of grade II obesity which is associated with mechanical loads on the knee joint causing inflammation and progression of KOA. After 5 months of prolotherapy treatment, strengthened quadricep muscle exercising and static cycle endurance exercising, she improved her pain, WOMAC score, and cardiorespiratory function. Hypertonic dextrose prolotherapy (HDP) is one of the choices for interventional therapy of its advantages, inexpensive, easily conducted, safe with minimal or even no recorded complications, and long-term efficacy even for grade IV of KOA like this patient.